Effects of a Hypercaloric and Hypocaloric Diet on Insulin-Induced Microvascular Recruitment, Glucose Uptake, and Lipolysis in Healthy Lean Men. Issue 7 (July 2020) - Emanuel, Anna L.; Meijer, Rick I.; Woerdeman, Jorn; van Raalte, Daniel H.; Diamant, Michaela; Kramer, Mark H.H.; Serlie, Mireille J.; Eringa, Etto C.; Serné, Erik H.
Abstract : Objective: In mice fed a high-fat diet, impairment of insulin signaling in endothelium is an early phenomenon that precedes decreased insulin sensitivity of skeletal muscle, adipose tissue, and liver. We assessed in humans whether short-term overfeeding affects insulin-induced microvascular recruitment in skeletal muscle and adipose tissue before changes occur in glucose uptake and lipolysis. Approach and Results: Fifteen healthy males underwent a hypercaloric and subsequent hypocaloric diet intervention. Before, during, and after the hypercaloric diet, and upon return to baseline weight, all participants underwent (1) a hyperinsulinemic-euglycemic clamp to determine insulin-induced glucose uptake and suppression of lipolysis (2) contrast-enhanced ultrasonography to measure insulin-induced microvascular recruitment in skeletal muscle and adipose tissue. In addition, we assessed insulin-induced vasodilation of isolated skeletal muscle resistance arteries by pressure myography after the hypercaloric diet in study participants and controls (n=5). The hypercaloric diet increased body weight (3.5 kg; P <0.001) and fat percentage (3.5%; P <0.001) but did not affect glucose uptake nor lipolysis. The hypercaloric diet increased adipose tissue microvascular recruitment ( P =0.041) and decreased the ratio between skeletal muscle and adipose tissue microvascular blood volume during hyperinsulinemia ( P =0.019). Insulin-induced vasodilation of isolated skeletal muscle arterioles was significantly lower in participants compared with controls ( P <0.001). The hypocaloric diet reversed all of these changes, except the increase in adipose tissue microvascular recruitment. Conclusions: In lean men, short-term overfeeding reduces insulin-induced vasodilation of skeletal muscle resistance arteries and shifts the distribution of tissue perfusion during hyperinsulinemia from skeletal muscle to adipose tissue without affecting glucose uptake and lipolysis. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02628301. Abstract : Supplemental Digital Content is available in the text.